SOCIAL-PSYCHOLOGICAL ASPECTS OF STUDYING ECOLOGICAL CONSCIOUSNESS - Akramov Mirmuxsin Rustamovich (American Journals Publishing, 2024)
This article is devoted to the topic of socio-psychological aspects of the study of environmental consciousness in the formation of an environmentally healthy environment. The text of the article also discusses the interaction of a person and the environment, the phenomenon of ecological consciousness and its description, consciousness and its development, personality in sociogenesis, ontogenetic development of ecological consciousness, ecological culture and human values, psychological features of the manifestation of ecological consciousness are widely covered.
Keywords: Personality, consciousness, ecological consciousness, psychology, environment, interaction, natural world, ecological culture, ethics, need, society, anthropopathism.